The abundant dietary constituent ferulic acid forms a wide range of metabolites including a glutathione adduct when incubated with rat hepatocytes. (6th November 2013) - Omar, Khaled; Grant, M. Helen; Henderson, Catherine; Watson, David G.
Abstract: 1. The metabolism of ferulic acid (FA) has been studied in a number of different systems and several metabolites of FA have been characterised. No previous work has been carried out using hepatocytes to characterise the metabolism of FA. 2. A metabolomics approach in combination with high resolution mass spectrometry was used to characterise the metabolites of FA formed in isolated rat hepatocytes. FA was incubated with rat hepatocytes and the metabolites formed were profiled at 30 and 120 minutes. The metabolites were characterised according to their accurate mass at <2 ppm using Fourier transform mass spectrometry (FT-MS). 3. Sixteen metabolites of FA were identified. The most abundant metabolite was the sulphate of FA and this was followed by FA glucuronide and glycine conjugates. A wide range of low level metabolites were produced in the hepatocyte incubations. Novel metabolites resulted from side chain oxidation. 4. In addition, a glutathione (GSH) adduct of FA was formed. Incubation of a solution of FA with GSH also resulted in formation of this adduct indicating that it could be formed purely by a chemical reaction. Thus the metabolism of FA in rat hepatocytes is more complex than previously described.